The Effect of the Hand and the Power Driven Rott Canal Rinse - M. Jurisa; L. Roubalíková (Czech Dental Chamber, 2006)
The authors compare the effect of the various methods of the rinse of the root canal. 12 extracted single root teeth were randomly dividend into 3 groups. The endodontic treatment was performed using hand instruments under standard conditions (EDTA gel in combination with 2% NaOCl). In the first group only hand rinsing was preformed, in the second group the special endodontic canila was used ane in the third group the power driven instrument Rinse Endo, DürrDental, Germany) was used. After the preparation the teeth were split longitudinaly and microscopically observed. The clean areas were quantified and the groups were compared statistically with the Fischer exact test (p=0,05). The cleanliness of the root canal walls was significantly better in the group where Rinse Endo was used.